2009
DOI: 10.1542/peds.2007-2872
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in the Incidence of Chronic Lung Disease in Very Low Birth Weight Infants: Results of a Quality Improvement Process in a Tertiary Level Neonatal Intensive Care Unit

Abstract: By using a quality improvement process that included avoidance of intubation, adoption of new pulse oximeter limits, and early use of nasal continuous positive airway pressure therapy, we demonstrated a significant reduction in the incidence of chronic lung disease in infants with birth weights of <1500 g in 2005, in comparison with 2002. These results have persisted to date. There were no significant short-term complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(37 citation statements)
references
References 31 publications
3
32
0
2
Order By: Relevance
“…Compared to non-EnCPAP neonates, EnCPAP neonates had reduced mortality, mechanical ventilation, BPD and PH, without an increased risk of pneumothorax. The lower rates of endotracheal intubation at birth and surfactant therapy despite more RDS in our EnCPAP neonates were similar to those reported by others [13,14,15,16,17,18,19,20,21]. Contrary to studies reported elsewhere, our EnCPAP neonates had a significantly lower mortality at discharge [3,4,22] and no increased risk of IVH [22].…”
Section: Discussionsupporting
confidence: 87%
“…Compared to non-EnCPAP neonates, EnCPAP neonates had reduced mortality, mechanical ventilation, BPD and PH, without an increased risk of pneumothorax. The lower rates of endotracheal intubation at birth and surfactant therapy despite more RDS in our EnCPAP neonates were similar to those reported by others [13,14,15,16,17,18,19,20,21]. Contrary to studies reported elsewhere, our EnCPAP neonates had a significantly lower mortality at discharge [3,4,22] and no increased risk of IVH [22].…”
Section: Discussionsupporting
confidence: 87%
“…14 The sustained improvements we observed in respiratory outcomes for VLBW newborns mainly occurred 1 year after implementation of bnCPAP, early surfactant treatment, and rapid extubation strategy, and continued to show improving trends in respiratory outcomes during the subsequent 3 years, consistent with similar improvements reported by others after several years of use. 11,17 Our study expands the VLBW population size and includes a larger number of VLBW babies and ELBW babies Ͻ 27 weeks gestational age.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these interventions were in line with current evidence-based practice recommendations and achieved by other QI efforts to reduce morbidities. 8,9,[21][22][23] Significant reductions in nosocomial infections and growth restriction were credited to consistent team application of practice. Although there were no specific process changes targeting a reduction in infection, usual processes, such as strict adherence to central line care and antibiotic stewardship, were further standardized by the team.…”
Section: Figurementioning
confidence: 99%